E-Learning and the National Broadband Network - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2019)
A recent paper from February 2013 foreshadowing the dynamic changes in e-Learning from Australia’s roll-out of the National Broadband Network.